Illumination in Serat Gada (Gonda) Kusuma Add Ms 12297 - Titis Pramadani (Javanologi: International Journal of Javanese Studies, 2024)
The article with the title Illumination in the Serat Gada (Gonda) Kusuma Add Ms 12297 contains a study of codicology that discusses illumination in the Serat Gada (Gonda) Kusuma. This study aims to analyze and identify the illumination of the Serat (Gonda) Kusuma. The research method used is descriptive analysis, the results of this study are that there are several illumination motifs and color ornaments. Illumination motifs include peacocks, jasmine flowers, Sri Fortune leaves, shiso leaves, and bamboo. As for the color ornaments, it consists of gold, red, green, yellow, blue, and white. The results of the analysis of illumination and color ornaments are that each illumination motif and color ornament has a good meaning, some of the illumination motifs and color ornaments describe a kingdom's prosperity and the courage of a leader or king, this is related to the text contained in the Serat Gada illumination (Gonda) Kusuma.